The Impact of Endovascular Rescue Therapy on the Clinical and Radiological Outcome After Aneurysmal Subarachnoid Hemorrhage: A Safe and Effective Treatment Option for Hemodynamically Relevant Vasospasm? - Mielke, Dorothee; Döring, Katja; Behme, Daniel; Psychogios, Marios Nikos; Rohde, Veit; Malinova, Vesna (Frontiers in Neurology, 2022)
Objective Cerebral vasospasm (CVS) represents one of the multiple contributors to delayed cerebral ischemia (DCI) in patients with aneurysmal subarachnoid hemorrhage (aSAH). Especially the management of CVS, refractory to medical treatment, is a challenging task during the acute phase after aSAH. Endovascular rescue therapies (ERT), such as medical and mechanical dilation, are possible treatment options on an individual basis. However, data about the influence on the patients' functional outcomes are limited. This study aims to assess the impact of ERT on the long-term functional outcome in aSAH-patients with refractory CVS. Methods We performed a retrospective analysis of aSAH patients treated between 2012 and 2018. CVS was considered refractory, if it persisted despite oral/intravenous nimodipine application and induced hypertension. The decision to perform ETR was made on an individual basis, according to the detection of “tissue at risk” on computed tomography perfusion (CTP) scans and CVS on computed tomography angiography (CTA) or digital subtraction angiography (DSA). The functional outcome was assessed according to the modified Rankin scale (mRS) 3 months after the ictus, whereas an mRS ≤ 2 was considered as a good outcome. Results A total of 268 patients were included. Out of these, 205 patients (76.5%) were treated without ERT (group 1) and 63 patients (23.5%) with ERT (group 2). In 20 patients (31.8%) balloon dilatation was performed, in 23 patients (36.5%) intra-arterial nimodipine injection alone, and in 20 patients (31.8%) both procedures were combined. Considering only the patient group with DCI, the patients who were treated with ERT had a significantly better outcome compared to the patients without ERT (Mann–Whitney test, p = 0.02). Conclusion Endovascular rescue therapies resulted in a significantly better functional outcome in patients with DCI compared to the patient group treated without ETR. CTP and CTA-based identification of “tissue at risk” might be a reliable tool for patient selection for performing ERT.